Oceans of crime maritime piracy and transnational security in Southeast Asia and Bangladesh - Liss, Carolin (IIAS/ISEAS series on maritime issues and piracy in Asia, 2011)
Southeast Asia and Bangladesh are at present global hot spots of pirate attacks on merchant vessels and fishing boats. This book explains why, and in what form, piracy still exists. It offers an integrated analysis of the root causes of piracy, linking declining fish stocks, organized crime networks, radical politically motivated groups, the use of flags of convenience, the lack of state control over national territory, and the activities of private security companies, and identifies their wider security implications.